Pelaksanaan Peraturan Daerah Kota Balikpapan Nomor 1 Tahun 2021 Tentang Perubahan Atas Peraturan Daerah Nomor 10 Tahun 2017 Tentang Penyelenggaraan Ketertiban Umum Oleh Satuan Polisi Pamong Praja Dalam Upaya Penertiban Gelandangan Anak Jalanan Dan Pengem - Baswanto Hukum; Elwidarifa Marwenny (GLOBAL SCIENTS PUBLISHER, 2025)
Enforcement of Balikpapan City Regional Regulation Number 1 of 2021 concerning the Implementation of Public Order is the obligation of the Balikpapan City regional government in order to implement public security and peace so that a sense of security and comfort is fulfilled for the Balikpapan City Community, however a number of public order problems are still in the spotlight of the Balikpapan City community such as the large number of street children, vagrants and beggars who roam in public places, both in restaurants and even at red lights which disturb residents even though Balikpapan City is a buffer for the National Capital. The limitations of the problem in the study include: 1) Implementation of Balikpapan City Regional Regulation Number 1 of 2021 concerning amendments to Regional Regulation Number 10 of 2017 concerning the implementation of public order by the Civil Service Police Unit in an effort to control vagrants, street children and beggars in Balikpapan City; 2) Supporting and inhibiting factors in the implementation of the duties of the Balikpapan City Civil Service Police Unit; and 3) The social impact felt by the Balikpapan City community due to the control carried out by the Balikpapan City Civil Service Police Unit against people with social welfare problems in Balikpapan City. The type of research used to describe the problem is empirical juridical using a statute approach and a case approach. Based on the results of the study, it can be concluded that: 1) The Balikpapan City Civil Service Police Unit has carried out its duties effectively in enforcing Balikpapan City Regional Regulation Number 1 of 2021; 2) The main obstacles faced are limited personnel and lack of facilities and infrastructure, lack of synergy between agencies and the permissive nature of society; and 3) The Balikpapan City Community has received a positive social impact on the existence of the Order of People with Social Welfare Problems in Balikpapan City